2008
DOI: 10.1136/tc.2007.024265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nationwide tobacco control policies on smoking cessation in high and low educated groups in 18 European countries

Abstract: Countries with more developed tobacco control policies have higher quit ratios than countries with less developed tobacco control policies. High and low educated smokers benefit about equally from the nationwide tobacco control policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 41 publications
8
126
3
3
Order By: Relevance
“…Past studies suggest that SES inequalities may be increasing: smoking cessation patterns over time show a trend toward increasing cessation in Asian Pacific Journal of Cancer Prevention, Vol 14, 2013 6923 DOI:http://dx.doi.org/10.7314/APJCP.2013.14.11.6919 National "Smoking Cessation Clinics" in Korea: Socioeconomic Status and Age Matter higher SES groups, along with increasing inequalities in smoking in Western countries (Gilpin et al, 2002;Jefferis et al, 2004;Chilcoat, 2009). Other European studies have found that, in general, SES inequalities in smoking and cessation are increasing among younger age cohorts and decreasing among older age cohorts (Federico et al, 2007;Schaap et al, 2008). Our Korean data show that SES inequalities in cessation increase throughout young and middle ages, and start to decrease only at age 60 or older.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies suggest that SES inequalities may be increasing: smoking cessation patterns over time show a trend toward increasing cessation in Asian Pacific Journal of Cancer Prevention, Vol 14, 2013 6923 DOI:http://dx.doi.org/10.7314/APJCP.2013.14.11.6919 National "Smoking Cessation Clinics" in Korea: Socioeconomic Status and Age Matter higher SES groups, along with increasing inequalities in smoking in Western countries (Gilpin et al, 2002;Jefferis et al, 2004;Chilcoat, 2009). Other European studies have found that, in general, SES inequalities in smoking and cessation are increasing among younger age cohorts and decreasing among older age cohorts (Federico et al, 2007;Schaap et al, 2008). Our Korean data show that SES inequalities in cessation increase throughout young and middle ages, and start to decrease only at age 60 or older.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, as suggested by some studies, because the rates of smoking cessation are lower in socioeconomically vulnerable populations, the differences in smoking rates between socioeconomic levels may have increased. 6,7 Several variables relating to sociodemographic conditions are closely connected with the likelihood of smoking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an intervention that reduces the number of cues in the environment by modifying tobacco advertising policies could be beneficial for Black smokers. 43 …”
Section: Discussionmentioning
confidence: 99%